Being a Minority in a Moslem Neighborhood: Reflective Experience of a Buddhist Priest in Cemani Village - Nusya Kuswantin (STAB Kertarajasa, 2022)
On Tuesday, 1st of October 2019 around 02.30 a.m., Amoghasiddhi Cetiya at Cemani Village, Grogol Subdistrict, Sukoharjo Regency, Central Java, Indonesia, was caught on fire for the second times. The carpet was scorched and the air-condition was fell-down. The crime was reported to the police, but the priest and his followers expect nothing but take it as a blessing in disguise that it’s the time for them to repaint and refurnish their prayer house. By applying interview, news research, limited participant observation and reflective-interpretive approach this paper tries to discuss and conclude that in order to be able to survive a religious minority group needs to equipt themselves with personal capacity such as high sense of tolerance, modesty, relenting attitude, and ignoring their rights to justice. Those are the challenges for religious minority groups to live in Indonesia, a country which is ethnically multicultural but ironically only six religions are sanctioned by the state with Islam as the one adhered by around 80% of the population. So then, discussing inter-faith relation will result in a bias conclusion as both majority and minority have their own syndromes. Feeling of fear or being threatened by the existence of something new is the syndrome for the majority, while relenting attitude as well as tendency not to demand their rights to with the fear that struggling for justice may lead to misfortune justice for the minority, as experienced by Meiliana of Tanjungbalai, North Sumatera. The Buddhist woman of Chinese ethnic was accused of committing blasphemy in July 2016 merely because she complaint the high volume of adzan prayer call from a neighbourhood mosque. Not only her house was then destroyed by a mob, but also more than tens of vihara in her town were set on fire. In April 2019 her appeal to Supreme Court was refused, so she has to serve 18 months jail sentence as verdicted.